1986
DOI: 10.1039/p29860000645
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the electronic states of amidyls: evidence for Π—Σ mixing in simple amidyls

Abstract: N-Methyl-and N-acetyl-biphenyl-2-carboxamidyls, generated from the corresponding Nbromides in photochemically initiated alkyl radical or bromine atom chain reactions, cyclise to give Ar,-5 and Ar,-6 products, indicating the accessibility of a low-energy excited C-state for these species. N-Methoxybiphenyl-2-carboxamidyl radical, from photolysis of the N-chloro derivative, yields no products from Ar,-5 or Ar,-6 cyclisation; this indicates a thermodynamically stable ll-ground state and a high-energy and thermall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…To overcome these limitations, we envisioned a new umpolung approach in which the initial oxidative dearomatization step would instead proceed via attack of an electron‐rich aromatic ring on an electrophilic side chain (Figure c) . This would allow a wider range of non‐phenolic substrates to be used and might also allow direct ring expansion from the nascent reactive intermediate in a tandem reaction (Figure a).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these limitations, we envisioned a new umpolung approach in which the initial oxidative dearomatization step would instead proceed via attack of an electron‐rich aromatic ring on an electrophilic side chain (Figure c) . This would allow a wider range of non‐phenolic substrates to be used and might also allow direct ring expansion from the nascent reactive intermediate in a tandem reaction (Figure a).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 These compounds were obtained by the ring closure of N-chloro hydroxamates 1 with silver tetrafluoroborate in anhydrous ether (Scheme 3). 1,2 These compounds were obtained by the ring closure of N-chloro hydroxamates 1 with silver tetrafluoroborate in anhydrous ether (Scheme 3).…”
Section: 1-benzoxazepinesmentioning
confidence: 99%
“…4a). Work in these laboratories and elsewhere has established that nitrenium ions are strongly stabilized by neighbouring heteroatoms (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Such a process would be promoted by polar solvents as well as acid or Lewis acid complexation with X.…”
Section: Reactivity Of Anomeric Amidesmentioning
confidence: 99%
“…A related class of analogues, the N,N ′-diacyl-N,N ′-dialkoxyhydrazines 12, are readily generated by oxidative dimerization of hydroxamic esters (37)(38)(39)(40) and by dimerization of alkoxyamidyl radicals formed upon oxidation of hydroxamic esters or photolysis of N-alkoxy-N-haloamides (41,42). In a recent study we have demonstrated that these hydrazines exhibit all the hallmarks of anomeric amides (15).…”
Section: Rearrangement Of the Intermediate N-alkoxy-n-(n-methyl-mentioning
confidence: 99%